"There is no time for rest": Gendered CSR, sustainable development and the unpaid care work governance gap. (27th September 2018) - McCarthy, Lauren
Abstract: Unpaid care work, including child care, elder care, and housework, is unremunerated work essential to human survival and flourishing. Worldwide, women disproportionally carry out this work, impacting upon their ability to engage in other activities, such as education, employment, or leisure. Despite a growing number of businesses engaging in "gendered CSR, " in the form of women's empowerment projects, attention to unpaid care work remains little discussed in the literature, despite its importance to sustainable development. Applying Diane Elson's feminist economic framework for alleviating unpaid care work inequality to a case study of gendered CSR in Ghana, I find that at present unpaid care work is (a) unrecognised in business' CSR, (b) may be both reduced or exacerbated by CSR efforts, and (c) remains conceptualised as relevant only to the private sphere, therefore, missing a unique opportunity for business to contribute to gender equality and sustainable development. Connecting unpaid care work and business responsibility contributes to a more expansive understanding of what CSR may be.